(untitled) (African Journal of Science, Technology and Social Sciences, 2022)
Introduction: Zoonoses are infectious diseases transmitted from vertebrate animals to humans. Persons with low knowledge and exposure to wildlife and domestic animals or their products are at higher risk. Extensive research and public health surveillance for timely response through One Health framework is necessary to stop possible cross-species pathogen exchange between animals and humans. This study compared the knowledge on zoonoses between residents at the wildlife-interface zone of Meru National Park, and non-wildlife areas of Tigania West Sub County, Meru Kenya. Methods: Data were collected simultaneously in both wildlife interface zone and non-wildlife zone and compared. Descriptive statistics were used to summarize the data for differences in awareness between the two areas. Results: The knowledge on zoonoses in the non-wildlife interface zone of Tigania West Sub-County was statistically significant at p< .05. Tigania West residents more aware of zoonoses than their counterparts living next to Meru National Park. χ² (1, N=525) =84.965, p< .001. Conclusion: The residents of Igembe Central had scanty knowledge on zoonoses despite closer proximity to the wildlife conservancy. This community was considerably at higher risk of contracting zoonoses than persons at the non-wildlife zones. Awareness creation through one health strategy is necessary as a deterrent measure.